A comparative study of the law relating to parental negligence as according to Section 33 of the Child Act and the law in the United Kingdom / Muhammad Fauzi Shahari and Nur Farhana Resat - Shahari, Muhammad Fauzi; Resat, Nur Farhana (2012)
This research looks on a comparative study between the laws in Malaysia and the UK concerning the issue of parental negligence. Parents are morally as well as legally obligated to exercise their duty of care on their children. Failure to meet the standard of care in their acts or omissions amounts to negligence. Due to the increase in the number of incidents of parental negligence reported in Malaysia, the legislature has come out with Child Act 2001 where it is provided that the failure to exercise reasonable care is an offence under the statute. Although parental negligence is an offence, the increase in the number of child neglect cases is a sign that something needs to be done with our legislation relating to the issue. In this research, apart from critically examining the legal provisions relating to child neglect in Malaysia and UK, we will also look into the international perspective. The study will focus on how to develop the current law on parental negligence so as to propose recommendations to the policy maker so that they can come out with a better legislation. This research will be conducted, in a qualitative method with library- based materials and online searching.